2020
DOI: 10.3390/life10090202
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Pepsin-Related Ocular Surface Damage and Dry Eye (PROD Syndrome) in Patients with Laryngopharyngeal Reflux

Abstract: Background: patients with laryngopharyngeal reflux (LPR) showed detectable levels of tear pepsin that explain the nasolacrimal obstruction. The purpose of this study was to determine whether patients with LPR show ocular surface changes and to investigate the relationship between lacrimal pepsin concentration and ocular alterations. Methods: Fifty patients with positive endoscopic signs for LPR and an equal or higher score of 13 and 7 for Reflux Symptom Index and Reflux Finding Score were enrolled. Twenty heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
(46 reference statements)
0
5
0
1
Order By: Relevance
“…There is also research showing that decreased serotonin levels, often found in psychiatric disorders, may also be associated with autonomic nervous dysregulation of lacrimal gland function and Reumatologia 2021; 59/5 with atrophy and autophagy of the lacrimal gland [6]. Frequent episodes of vomiting in patients may also be an important factor in the development of subjective symptoms of DES because, according to current data, gastro-oesophageal reflux disease may be associated with the development of ocular surface diseases and, in particular, with the development of dry eye [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also research showing that decreased serotonin levels, often found in psychiatric disorders, may also be associated with autonomic nervous dysregulation of lacrimal gland function and Reumatologia 2021; 59/5 with atrophy and autophagy of the lacrimal gland [6]. Frequent episodes of vomiting in patients may also be an important factor in the development of subjective symptoms of DES because, according to current data, gastro-oesophageal reflux disease may be associated with the development of ocular surface diseases and, in particular, with the development of dry eye [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…The patient was subsequently referred to an ophthalmologist, with complaints of persistent redness and dryness of both eyes for the past 2 years. For dry eye evaluation complete ophthalmologic examination included the Schirmer test, slit-lamp examination for assessment of tear break-up time (TBUT), and ocular surface fluorescein staining [6][7][8]. Diagnostic ophthalmological tests revealed complex myopic astigmatism and mild amblyopia with best corrected visual acuity of 20/60 in the right eye and 20/40 in the left eye.…”
Section: Case Descriptionmentioning
confidence: 99%
“…Studies have found that, in patients with dry eye disease, there was a local increase of eye pepsin concentration [59,63], which is postulated to have travelled into the lacrimal system via the nasal cavity, inferior meatus, or nasolacrimal duct, and this may affect ocular surface though its direct proteolytic activity and the local expression of proinflammatory cytokines [65]. A study of 50 patients with LPR, proven both endoscopically and via symptom indices, found that tear pepsin levels correlated significantly with the severity of the LPR disease and ocular surface changes [66]. Pepsin, a serine-protease, can cause direct erosion of the mucosa and elicit hyperaemia and irritative symptoms, while at the same time inducing the production of pro-inflammatory cytokines; hence, it is postulated to similarly promote inflammatory cytokines when present on the ocular surface [61,66].…”
Section: Gut Microflora Laryngopharyngeal Reflux (Lpr) Diseasementioning
confidence: 99%
“…O conteúdo gástrico é constituído de vários elementos, dentre eles, a pepsina, uma enzima liberada pelo estômago durante o processo de digestão. Essa enzima foi documentada nas lágrimas de pacientes com RLF e associada a sintomas de desconforto ocular, à diminuição da estabilidade do filme lacrimal e hiperemia conjuntival (MAYO-YÁÑEZ et al, 2021;PLATEROTI et al, 2020).…”
Section: Queixas Oftalmológicasunclassified